Governance institutions and economic development emerging China, India, East Asia and Brazil - Roy, Kartik Chandra 1941- (World Scientific Publishing Company Pte Limited, 2018)
"With over three decades worth of research and analysis, Roy compares ten countries - India; Brazil; Indonesia; China; Japan; South Korea; Singapore; Vietnam; Thailand; and, Malaysia - in the role of the state in economic development. Comprising of a rich body of work on state intervention and developmental states, Roy postulate on the idea of 'virtuous' and 'vicious' interventionist states."--